PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PERKEBUNAN HASIL MUSI LESTARI JAYALOKA KABUPATEN MUSI RAWAS - Aning Kesuma Putri; Siti Holia (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
This studyaims to find out How to Influence Communication and Work Environment Against Employee Productivity at PT. Results plantation Musi Lestari Jaya loka Musi Rawas .In this study,the population in question is employees at PT. Results plantation Musi Lestari Jaya loka Musi Rawas totaling 40 people. The results showed that the variables Communication significant effect on Employee Productivity at PT. Results plantation Musi Lestari Jaya loka Musi Rawas. From the results ofthis study indicate that the Communication and the Working Environment influence Employee Productivity at PT. Results plantation Musi Lestari Jaya loka Musi Rawas.